Cidofovir, a choice for salvage treatment of cytomegalovirus infection in patients with haploidentical hematopoietic stem cell transplantation. Issue 2 (24th February 2022) - Yin, Zhao; Sun, Jing; Yang, Ying; Xu, Na; Jiang, Ling; Fan, Zhiping; Huang, Fen; Shi, Pengcheng; Wang, Zhixiang; Xuan, Li; Xu, Jun; Liu, Qifa; et al.
Abstract: Background: Cidofovir (CDV) is a nucleotide analogue with broad antiviral activities. It remains unclear about the CDV administration for anti‐cytomegalovirus (CMV) treatment in patients with haploidentical hematopoietic stem cell transplantation (haplo‐HSCT). Patients and methods: In this study, 31 out of 101 haplo‐HSCT recipients who suffered CMV infection in the CT group (conventional treatment) were enrolled into the CDV‐ST group (CDV second‐line treatment). These patients were treated with CDV as they failed conventional treatment or they were unavailable to the preemptive antiviral therapy. Nine patients with CMV infection were enrolled into the CDV‐FT group (CDV‐frontline treatment) and received CDV preemptive therapy. Results: In the CDV‐ST group, 23 of 28 (82.1%) patients were observed treatment response with a median time of 9 (2–23) days, and 20 (71.8%) among these patients obtained complete response (CR). In the CDV‐FT group, six of eight (75.0%) patients acquired CR with a median of 6 (4–25) days. The treatment response in CDV‐treated groups was comparable with those in CT groups. Besides, there was no statistical difference in CMV‐related mortality between the three groups ( p  > .05). During the follow‐up period (median follow‐up:10 [1–28] months), a total of 8 of 22 (36.4%) patients experienced CMV reactivation in the CDV‐ST group versus 23 of 62 (37.1%) in the CT group ( p  > .05). CDV‐related toxicities occurred in 13 of 40 (32.5%) patients, including six (15%) reversible nephrotoxicity. Conclusion: Our study suggests that CDV is potentially an option for the salvage treatment of CMV infection in the haplo‐HSCT patients.